Non-steroidal hormonal levels during ante and post-partum periods in goats - LEELA, V; SUGANYA, G; THANGAVEL, A; VISWANATHAN, S (The Indian Journal of Animal Reproduction, 2023)
Estimations of T3' T4, insulin, growth hormone were carried out in twelve Tellicherry goats byRIA. Results indicated that T3 and T4 were increased on the day of parturition and there after. Theinsulin showed a declining trend up to 10 day after postpartum, whereas the growth hormone showeda steady increase from day preparturn till 15th day parturitio.
Keywords: T3; T4; Insulin; Growth hormone; Prepartum and Postpartum; Tellicherry goats